Leveraging gamification for tourism marketing activities: Towards a comprehensive conceptual model - Malik, Garima; Sharma, Piyush; Pradhan, Debasis (SAGE, 2024)
Gamification has become one of the most effective ways to generate customer engagement. However, there needs to be more structured research on the drivers of the adoption and sustained use of gamification in travel and tourism research. Drawing upon the uses and gratifications theory and the technology acceptance model, this research examines the individual motivational drivers for adopting gamification in the context of tourism services. We employed a combination of partial least squares—structural equation modeling and fuzzy set qualitative comparative analysis on the data gathered from 680 users of various online travel agencies. Our findings show that individual motivational dimensions of uses and gratifications significantly influence perceived usefulness and ease of use in gamified marketing activities. Our analysis demonstrates five configurations leading to a high level of adoption of gamified marketing activities. This study extends the use of gamification in the tourism industry, offering insights into enhancing customer motivations for adopting and effectively utilizing game mechanics and dynamics in marketing activities. Furthermore, through a novel framework, this study advances the uses and gratification theory at the intersection of gamification research and tourism literature.